Hemokonsentrasi dan Trombositopenia pada COVID-19, Pembelajaran dari Ruang Instalasi Gawat Darurat - Dani Rosdiana; Marlina Tasril; M Firdaus J Karimi (Jurnal Ilmu Kedokteran, 2023)
Coronavirus disease 2019 (COVID-19) has become a pandemic since January 2020 and caused the death of 6 million people by April 2022. Exponential human-to-human transmission and the wide variety of clinical and laboratory manifestations of COVID-19 were challenging. Hematological abnormalities such as thrombocytopenia and hemoconcentration in COVID-19 are difficult to distinguish from dengue fever in the ER. Misdiagnosis would impact patient outcomes, health workers, and community safety as well as its transmission. We report a suspected case of dengue fever in admission in X Pekanbaru hospital, Riau which is confirmed as COVID-19. The patient was observed in the isolation ward and treated accordingly to the COVID-19 protocol and heparin due to coagulopathy related to COVID-19. The Proper initial assessment of acute febrile, especially Dengue fever at the emergency room, and the availability of modalities in diagnosing COVID-19 are of paramount importance in the era of the COVID-19 pandemic, even more, it become endemic status.